Horizontal gene transfer can facilitate the formation of stable and diverse microbial communities: an in silico agent-based model - Juhász, János; Jády, Attila; Ligeti, Balázs (22nd Annual International Conference, RECOMB 2018, 2018)
Microbial communities populate nearly every habitat of the Earth including the inner and outer surfaces of other organisms, for example the human digestive track. These communities can be stable in spite of consisting of multiple bacterial species that are competing for space and nutrient sources and often produce multiple antimicrobial factors against each other. We constructed an in silico agent-based computational model to study the effects of antimicrobial factors to microbiome stability and the possible defence mechanisms against them. Our results suggest that horizontal gene transfer of antimicrobial factor resistance genes can facilitate the formation and stability of diverse microbial communities. These diverse communities perform various biochemical tasks while their members are resistant to the repertoire of factors produced by community members. In contrast, foreign bacteria, for example external pathogens are sensible to the collection of antimicrobials secreted by the community. In addition to the previous territorial defence mechanism the horizontal gene transfer model also supports microbial therapy: a diverse community can purge out a less divers microbiome dominated by for example a multiresistant opportunistic pathogen like Clostridium difficile.